Spin‐Selective Full and Subtle Light Intensity Manipulation with Diatomic Metasurfaces. Issue 5 (18th December 2022) - Cheng, Jiaqi; Li, Zhancheng; Choi, Duk‐Yong; Yu, Shiwang; Liu, Wenwei; Wang, Haoyu; Zhang, Yuebian; Cheng, Hua; Tian, Jianguo; Chen, Shuqi
Abstract: Metasurfaces are considered to be ideal candidates for precise and continuous manipulation of optical wave intensity at nanoscale pixels, which is the main basis of display and imaging devices. Malus's law has been widely used as the basic design principle for the realization of linearly polarized optical wave intensity manipulation. However, there is no such straightforward and concise law like Malus's law that can be used to design metasurfaces for full and subtle intensity manipulation of circularly polarized optical waves. Here, a new design strategy based on the collective interference effect in diatomic metasurfaces is presented to fill this gap, which can create a simple and complete mapping from a single structural variable to the reflection intensity of circularly polarized waves. The full and subtle intensity manipulation of circularly polarized optical waves can be conveniently realized by changing one structural parameter in the diatomic metasurface. Spin‐selective high‐level grayscale images are numerically and experimentally implemented based on the proposed diatomic metasurfaces. The proposed grayscale imaging scheme with subwavelength spatial resolution and high gray level is promising for advanced display and information encryption applications. Abstract : Spin‐selective full and subtle intensity manipulation of circularly polarized waves is numerically and experimentally realized by utilizing diatomic metasurfaces and simply changing one structural parameter. The potential application of the proposed diatomic metasurfaces in spin‐selective high‐resolution and high‐level grayscale imaging has been demonstrated, promising further applications in advanced display and information encryption.